Making and Unmaking in Early Modern English Drama Spectators, Aesthetics and Incompletion - Porter, Chloe (Manchester University Press, 2014)
Exploring the significance of visual things that are 'under construction' in works by playwrights. Illustrated with examples, it opens up new interpretations of the place of aesthetic form in the early modern imagination. Why are early modern English dramatists preoccupied with unfinished processes of 'making' and 'unmaking'? And what did 'finished' or 'incomplete' mean for spectators of plays and visual works in this period? Making and unmaking in early modern English drama is about the prevalence and significance of visual things that are 'under construction' in early modern plays. Contributing to challenges to the well-worn narrative of 'iconophobic' early modern English culture, it explores the drama as a part of a lively post-Reformation visual world. Interrogating the centrality of concepts of 'fragmentation' and 'wholeness' in critical approaches to this period, it opens up new interpretations of the place of aesthetic form in early modern culture.